Analysis of blood flow in pulmonary hypertension with the pulsed Doppler flowmeter combined with cross sectional echocardiography. Issue 4 (April 1984) - Okamoto, M; Miyatake, K; Kinoshita, N; Sakakibara, H; Nimura, Y
Abstract : Blood flow patterns were analysed at nine points in the pulmonary area using the pulsed Doppler technique combined with cross-sectional echocardiography in 53 patients with heart disease and 10 healthy subjects. In subjects with a normal pulmonary artery pressure the blood flow pattern in systole showed a gradual acceleration and deceleration with a rounded summit in mid systole, designated the round type. In patients with pulmonary hypertension it showed a rapid acceleration and early deceleration with a sharp peak in early systole, designated the triangular type. The acceleration time index, defined as the ratio of the time interval from the beginning to the peak of ejection to the ejection time, showed a significant inverse correlation with mean pulmonary artery pressure. In pulmonary hypertension a prominent reverse flow occurred in the right posterior part of the pulmonary trunk during mid-systole and early diastole, indicating the presence of a vortex. Similar flow patterns were also seen in patients with idiopathic pulmonary artery dilatation. The factors responsible for the triangular type were principally the reduced capacitance and increased impedance of the pulmonary vascular tree. Those responsible for the reverse flow were the curved path of the blood flow and dilatation of the pulmonary artery.